Periparturient rise in the Cryptosporidium oocyst count in Beetal goats and evaluation of infection in new born kids - KHURSHEED, A; YADAV, ANISH; RAFIQI, SHAFIYA IMTIAZ; KATOCH, R; GODARA, R; SOOD, S; SALEEM, T (The Indian Journal of Animal Sciences, 2018)
In cryptosporidial infection, very scarce literature is available about periparturient pattern of oocyst excretion in goats and its implications in the epidemiology of disease in kids; thus the present investigation was done. Faecal samples (160) were examined from 20 pregnant goats, collected at weekly interval, commencing from 4 weeks before kidding up to 3 weeks after kidding. Faecal sample examination by Sheather’s floatation sedimentation technique followed by modified Ziehl-Neelsen staining technique revealed an overall positivity of 26.25% for Cryptosporidium oocysts. Prevalence of oocysts excretion was high around parturition and the number of oocysts shed oscillated between 20–400 oocysts/g (OPG) of faeces. Examination of 60 faecal samples of 20 kids born to studied goats from 1 to 3 weeks of age revealed 40% samples positive for Cryptosporidium oocysts and 65% kids became infected by the end of the 3 weeks. The OPG of kids ranged from 100 to 1,560. Molecular characterization by PCR-RFLP of 18S small subunit (SSU) rRNA gene showed that 73.80% and 26.19% goat samples, and 87.5% and 12.5% kids samples were positive for C. parvum and C. ubiquitum, respectively. The study indicated periparturient transmission of Cryptosporidium spp. from pregnant goats to their new born kids.